Tax Audit: Implementation of Compliance Risk Management - Dewa Ayu Made Kislina; Suparna Wijaya (Gorontalo State University, 2022)
In 2011, the OECD published a Compliance Risk Management (CRM) guide that countries worldwide can use to mitigate the level of taxpayer compliance risk. In 2019, the Directorate General of Taxes began implementing a national-scale CRM using computerization, especially in tax audits. Using the Compliance Risk Management model in tax audit activities is a step forward because the Directorate General of Taxes has implemented technology according to OECD recommendations. This study aimed to determine the tax audit system before and after implementing the Compliance Risk Management (CRM) model and assess the impact of implementing the Compliance Risk Management model on tax audit activities in Indonesia. This study also aims to determine the obstacles and effects of implementing Compliance Risk Management (CRM) on tax audits in Indonesia. This research is a qualitative descriptive study with data collection methods through library research and interviews. The results of this study reveal that implementing the Compliance Risk Management (CRM) model has a positive impact, especially on the process before the tax audit. The Compliance Risk Management (CRM) model can help to set priorities based on the level of taxpayer risk.